A Paradigm in the Evolution of the Proportion Science of Sūrahs; the Case Study of the Proportion of the Sūrahs “al-Fath and Muhammad” - Sedigheh Janati Firouzabadi; Ahmad Zare Zardini; Kamal Sahraei Ardakani (آموزه‌های قرآنی)
The knowledge of the proportion of the Quran sūrahs and attempt for performing more accurate study of the geometry structure of it for the different exegetical and theological utilizations is of the Quran (modern) contemporary researchers’ concerns. One of the research backgrounds for it is to know and put the findings of the non-contemporary and modern Quran scholars together and creating results in these Quranic sciences. Of the old approaches in the proportion science of the Quran surahs is linear study or the chronology of the surahs and the proportion of the surahs which totally contains a linear look in it. Today this look has continuously been followed. This research aims to promote this approach in the study of the holy Quran structure with putting the findings of the non-contemporary and modern Quran scholars together and to apply it in the analysis of the relationship between the sūrahs “Muhammad” and “Fath”. The findings show that there are different types of verbal and semantic relationship between these two surahs in the two micro and macro areas. It can be implied that the outcomes of this research which can be implied are: establishing a better background for perceiving these two sūrahs, a better knowledge and determination of the textual structure of the holy Quran and also presenting arguable answers to doubts about the multi layers of the Quran structure (text) and determination of the aesthetics of the holy Quran statement.